En bloc resection of proximal fibular giant cell tumour in skeletally immature patients with common peroneal nerve neuropraxia: a retrospective case series of 20 patients with one-year follow-up - Das, Mrinmoy; Dhakar, Mukesh; Meena, R. P.; Kumawat, Satish (International Journal of Research in Orthopaedics, 2026)
Giant cell tumour (GCT) of bone is rare in skeletally immature patients, and its occurrence in the proximal fibula presents unique challenges due to the risk of common peroneal nerve (CPN) injury and knee instability. This retrospective case series included 20 skeletally immature patients (≤18 years; mean age 16.35 years) with histologically confirmed proximal fibula GCT and preoperative CPN neuropraxia treated between September 2023 and August 2024 using en bloc (Malawer type I) resection with reattachment of the lateral collateral ligament (LCL) and biceps femoris. At a minimum 12-month follow-up, outcomes assessed included CPN recovery, recurrence, knee stability, MSTS score, complications, and return to school/sports. There were eight males and twelve females (right: left=9:11); 16 (80%) had Campanacci grade II and 4 (20%) grade III lesions, with a median symptom duration of seven months. All underwent resection with negative margins, and the mean operative time was 72 minutes. At 12 months, 17 patients (85%) achieved complete CPN recovery (mean 9 months), and 3 (15%) had partial recovery, with no persistent palsy or recurrence. The mean MSTS score was 28.6±1.87, and 17 knees (85%) were stable while 3 (15%) showed grade I varus laxity. Median return to school and sports were 28 and 32 weeks, respectively. Complications included two superficial infections and one wound debridement, with no permanent deficits. These findings indicate that en bloc resection with nerve preservation and lateral stabiliser reattachment provides excellent oncological control and functional outcomes in skeletally immature patients with proximal fibula GCT and preoperative CPN neuropraxia.